Barriers to and facilitators of the implementation of pharmacist services in primary care clinics: a scoping review protocol. Issue 1 (11th January 2022) - Li, Haixin; Liang, Xujian; Wang, Yang; Lu, Yiting; Deng, Zhiling; Ye, Yuanqu; Qian, Yi; Guo, Yi; Xu, Zhijie
Abstract : Introduction: Inappropriate medication use is a leading cause of avoidable harm in health systems and is particularly severe in primary care settings. Evidence has shown that the integration of pharmacists into primary care clinics has favourable satisfaction and effectiveness in health outcomes. However, barriers to and facilitators of pharmacist services in these settings have not been comprehensively reviewed. Therefore, this scoping review aims to map and examine the literature available on the barriers to and facilitators of the implementation of pharmacist services in primary care clinics to guide future implementation research. Methods and analysis: This scoping review will be undertaken following the six-stage framework developed by Arksey and O'Malley and be guided by recommendations by Levac et al . Eight electronic databases (PubMed, Embase, Scopus, Web of Science, CINAHL, PsycINFO, CNKI and Wanfang) will be searched. Reference lists and related citations, and grey literature from websites will be searched manually. Available information that has been reported in Chinese or English up to 31 August 2021 will be included. Studies will be selected and screened by two reviewers independently. Findings from the included studies will be extracted by two independent reviewers and supervised by a third reviewer. A content analysis of the findings will be performed using MAXQDA 2020. Ethics and dissemination: Ethical approval will not be required for this scoping review, as all data and information will be obtained from publicly available literature. The findings of this scoping review will be shared with healthcare managers in primary care institutions and health authorities as well as disseminated via publication in a peer-reviewed journal.